Responses to earlier literature in research article introductions: A rhetorical study in applied linguistics - Warsidi Warsidi; Abd Halim; Alfiandy Kamal; Nur Mutmainna Halim; Zifirdaus Adnan; Iskandar Abdul Samad; Andi Muhammad Irawan (Universitas Syiah Kuala, 2025)
Given that researchers aim to publish in prestigious journals, understanding the rhetorical organization of such publications is crucial. While this topic has been extensively studied, existing research has yet to explore how authors in reputable journals engage with prior literature. To fill this gap, the present study intends to analyze how research article authors respond to other earlier literature in their research article introductions (RAIs) published in reputable international applied linguistics journals. This study aims to achieve two objectives: to find out to what extent responding to other earlier literature is important in RAIs, and to discover what types of response authors employ in their RAIs. To achieve these goals, this study employed combined descriptive qualitative and quantitative approaches for analyzing 40 RAIs published in Q1 journals as data sets in the present study. Then, a new analytical framework was designed to respond to the above objectives. The results indicated that responding to other earlier literature is obligatory in RAIs published in reputable international applied linguistics journals. In responding to other earlier literature, authors employed three types of response: either extending other earlier studies, modifying other earlier studies, or establishing a new method, idea, or knowledge. This study offers theoretical contributions by expanding the understanding of how research article authors engage with prior literature within their RAIs. Its practical implications include guiding researchers on effectively utilizing prior literature to establish their research agenda when publishing in reputable journals.